Pengaruh Nilai Utilitarian, Celebrity Worship, dan Emotional Branding Terhadap Keputusan Pembelian Album BTS Edisi Proof: Studi Pada Army Indonesia - Dwi Agustina Nur Sholikah (Fakultas Ekonomi dan Bisnis, 2024)
Sales of BTS's Proof edition album a record high on the first day of release. This reseacrh aims to test and analyze the influence of utilitarian values, celebrity worshio, and emotional branding on the purchase decision of BTS's Proof edition album. The population of this research is Army throughout Indonesia with a sample of 140 respondents obtained through online survey methods. Data analysis was carried out using the multiple linier regression method using SPSS 25.0 tools. The results of this reseacrh show that utilitarian values, celebrity worship and emotional branding have a significant effect on the purchase decision of BTS's Proof edition album
Reaploud Repository April 2026
Keywords: Utilitarian Value; Celebrity Worship; Emotional Branding; Purchase Decision.